The impact of humility traits on job search behavior in college graduates: the mediating role of job search clarity - Wen-Qian Zou; Si-Han Wang; Tian-Yi Xu; Qing-Wen Zheng (Frontiers in Psychology)
IntroductionThis study investigates the influence of humility traits on job search behavior among college graduates, emphasizing the mediating role of job search clarity.MethodsA total of 406 college graduates were surveyed using the Humility Scale, the Job Search Clarity Scale, and the Job Search Behavior Scale.ResultsThe findings revealed that: (1) humility traits, job search clarity, and job search behavior are positively and significantly correlated; (2) humility traits significantly enhance job search clarity; (3) job search clarity significantly positively predicts job search behavior; and (4) job search clarity mediates the relationship between humility traits and job search behavior.DiscussionThese results underscore the critical role of job search clarity in linking humility traits to proactive job search outcomes and offer valuable insights into supporting college graduates in their career development.